The Truth Is Out There: The Prevalence of Conspiracy Theory Use by Radical Violent Extremist Organizations - Rousis, Gregory J. (Terrorism and political violence, 2022)
This project examined conspiracy theory use across three types of groups: radical violent extremists (RVE), nonviolent extremists, and moderates. Using the theory of significance quest, or the desire for one’s life to have meaning, the current project determined whether RVE groups were more likely to use conspiracy theories and promote loss of significance in violent passages than the other groups. Using text analysis software, researchers coded passages from six groups—two from each level of extremism—for conspiratorial and/or violent content. RVE groups were significantly more likely than the other groups to use conspiracy theories and promote violence. This pattern held for groups focused on radical Islamic fundamentalism as well as white supremacy groups. The pattern was more complex for loss of significance: in violent passages, neo-Nazis were significantly more likely than ISIS and Al Qaeda to promote loss of significance. Implications of the findings are discussed.